The effectiveness of animal physiology practical book based on guided inquiry model - Rina Widiana; Diana Susanti; Silvi Susanti; Ramadhan Sumarmin (University of Muhammadiyah Malang, 2019)
The effectiveness of animal physiology practical book based on guided inquiry model is the essential factor to achievement student understanding a about animal physiology concepts. The purpose of this study was to observe the effectiveness of animal physiology practical book based on guided inquiry model in Padang State University. The variables measured were affective, cognitive, psychomotor, and students’ activities. The data of this pre-experimental research were analyzed using averaged, percentage and standardized with Institutional assessment criteria. The results showed that the mean values were: 90.56 for affective competency (Criteria A), 82 for knowledge (Criteria A), and 89.66 for skills (Criteria A). Meanwhile, the percentage of student activities was 90.74% with very active category. It can be concluded that the effectiveness of practical book based on guided inquiry model was very effective to optimized student competences.